Digestibility, fermentation and rumen microbiota of crossbred heifers fed diets with different soybean oil availabilities in the rumen - Fiorentini, G. [UNESP]; Messana, J. D. [UNESP]; Dian, P. H M [UNESP]; Reis, R. A. [UNESP]; Canesin, R. C. [UNESP]; Pires, A. V.; Berchielli, Telma Teresinha [UNESP] (Elsevier, 2013)
The goal of this study was to evaluate the effects of different soybean oil availabilities on the intake and partial and total digestibility of dry matter (DM) and nutrients, rumen fermentation parameters, efficiency of microbial synthesis, and the rumen microbiota of crossbred beef heifers. Nine crossbred heifers fitted with rumen and duodenal cannulae were evaluated in a triple 3 × 3 Latin square design with three treatments and three periods in three simultaneous repetitions. Heifers approximately 18 months old, with mean initial and final body weights of 316.3±28.8 and 362.6±34.4 kg, respectively, were fed a diet containing 600. g/kg of corn silage and 400. g/kg concentrate with a 58.0. g/kg fat content in the total diet. The sources of lipids included soybean grain, rumen-protected fat, and soybean oil. The statistical analyses were conducted using PROC MIXED from SAS, and the means were compared using Tukey's test (P<0.05). Dietary lipid sources did not affect nutrient intake (P>0.05). Except the apparent digestibility of organic matter (P=0.024), the apparent digestibility of the other nutrients did not differ among the treatment groups. Regarding body nitrogen retention, the soybean grain treatment was more effective than the rumen-protected fat treatment (P=0.045); however, the soybean oil treatment did not differ from the other two treatments. In relation to the efficiency of microbial protein synthesis (g. N/kg of organic matter apparently digested in the rumen corrected for microbial organic matter), the soybean oil and soybean grain treatments were more efficient than the rumen-protected fat treatment (P=0.001). Animals fed rumen-protected fat had larger numbers of protozoa (P<0.001) and fungi (P<0.001) than those supplemented with soybean grain and soybean oil. The dietary lipid sources did not affect pH, the molar concentration of propionate and total volatile fatty acids (P>0.05), whereas the concentrations of ammonia nitrogen and acetate were higher in animals fed with rumen-protected fat than in those submitted to the other treatments. The use of different soybean oil availabilities did not affect nutrient intake; however, treatments with soybean oil and soybean grain were more efficient regarding nutrient intake than rumen-protected fat because they reduced the numbers of fungi and protozoa and consequently improved the efficiency of microbial protein synthesis. © 2013 Elsevier B.V.
Keywords: Bacteria; Fungi; Protozoa; Rumen-protected fat; Soybean grain; Soybean oil; Animalia; Bacteria (microorganisms); Glycine max; Zea mays